Ownership concentration, control, and capital structure in family and non-family firms - Pacheco, Luís Miguel (2022)
The objective of this paper is to empirically examine the relationship between the firm’s ownership and control structure and its leverage. Capital structure is not only the result of various financial characteristics of the firm but also depends on who is in control. Thus, it is fundamental to understand the influence that certain features of the shareholding structure or the composition of the board, including the potential differences between family and non-family firms, exert on capital structure decisions. The paper uses a sample of wine firms in Portugal, because it helps to capture a business sector where family firms make up a significant portion of the industry. It is used an unbalanced panel data set of 460 firms for the period 2010 to 2018 and applied a random-effects model specification. Our results do not evidence significant differences between family and non-family firms. Still, they indicate that firms with fewer shareholders, smaller boards, and where the main director or member of the board is also a shareholder tend to present higher debt levels. There is no evidence of a non-monotonic relation between the ownership structure and debt, nor the presence of moderating effects on that relation. This paper fills a gap in the literature as the impact that specific characteristics of firms and their leaders have on capital structure decisions is still a topic less studied in the literature, particularly in bank-based economies.